Diagnostic performance of different fluorescence systems on occlusal caries of permanent teeth correspondence - Alkan Elif; Mücahit Akça Arif; Şeker Merve; Meşeli Simge; Kargül Betül; Tağtekin Dilek; Yanikoğlu Funda; Çelik Zeynep Ceren (Balkan Stomatological Society, 2023)
Background/Aim: Evaluating the performance of two fluorescence-based methods on the detection of occlusal carious lesions in permanent teeth, compared with visual inspection and radiographic examination was the aim of this study. Material and Methods: Occlusal surfaces of 150 extracted human permanent molars were examined by two researchers using the International Caries Detection and Assessment System ll (ICDAS-II), FluoreCam (Daraza) and DIAGNOdent Pen® (KaVo). Standardized periapical radiographs were taken. The teeth were sectioned for histological validation and examined under 25x magnification under a stereomicroscope (Leica M27.5) using Downer criteria 0-4 as the gold standard. The correlation of diagnostic methods with histological analyses was evaluated using Spearman's rank correlation coefficients (rho). Results: All teeth were scored from 0 to 6 for ICDAS-II. The highest correlation of the gold standard was found with ICDAS-II followed by FluoreCam and DIAGNOdent Pen®. The association strength of ICDAS-II, Radiography, FluoreCam and DIAGNOdent Pen® with the histological evaluation was quite strong (p<0.05). Both fluorescence-based methods performed similarly. Conclusions: Radiograph is not specific for early carious lesions but may be used as an adjunct method for dentin caries. ICDAS-II classification is an accurate method for clinical examination of occlusal caries however additionally using fluorescence as a quantitative and visual examination is quite supportive and reinforcing especially for detecting enamel caries lesions.